Engaging economics and traffic engineering students in community issues using the MultiCreation approach - Renata Petrevska Nechkoska; Daniela Koltovska Nechovska; Marjan Angeleski (Naše gospodarstvo / Our Economy, 2021)
Effective teaching methods for the coming generations of pragmatic students and teachers are evolving towards much greater involvement on all sides, attempting to bridge real life and academia in innova-tive ways. Our theoretical foundation lays upon the Triple Helix, n-Tuple Helix theory and the innova-tion triangle, but in a problem-based multidisciplinary setting. After introducing and validating the Mul-tiCreation approach in teaching/learning for the business-academia collaboration, where multiple disci- plines, diverse profiles of students, professors, and managers have taken up various roles to address relevant business issues, we were encouraged to expand its applicability beyond the business world - toward societal problems. We retained the problem-b ased and participatory learning but shifted the positioning of the problem towards the safety of primary school children, incorporating economic, pro-ject-based, managerial, traffic engineering, logistical, regulatory, and governance issues. By including two primary schools, collaborating with their principals, advisory teams, and teachers, as well as chil-dren and parents, in two different cities, we aimed to provide complete research, engineering and educa-tion for the stakeholders so that the schools could just hand in documentation to the relevant municipal bodies to be acted upon effectuation. The involved students came from two faculties - of economics and traffic engineering, steered by three university professors on the subjects of project management and basic and advanced techniques for traffic management. The blended learning components took place as prescribed in the MultiCreation approach, during two semesters of two academic years. They combined countermeasures and solutions. The MultiCreation approach has been enhanced regarding its components and workflow and its effectiveness has been validated in a multi-stakeholder environ-ment of direct and indirect educational beneficiaries.
Keywords: A12; D78; O35; R41; 330; Problem-based learning; participatory learning; MultiCreation approach; Traffic Engineering; community-academia collaboration